Streptococcus agalactiae isolated from clinical mastitis cases on large dairy farms in north China: phenotype, genotype of antimicrobial resistance and virulence genes - Liu, Kai; Liu, Xiang; Yang, Jieyan; Gu, Xiaolong; Zhang, Limei; Qu, Weijie (Frontiers in Cellular and Infection Microbiology, 2024)
Streptococcus agalactiae (Strep. agalactiae) is bovine mastitis pathogen and has thus became a matter of concern to dairy farms worldwide in terms of economic loss. The aims of this study were to (a) determine virulence genes, and (b) characterize the antimicrobial resistance (AMR) profiles and AMR genes and (c) figure out the relationship between AMR phenotypes and genotypes of Strep. agalactiae isolated from dairy cows in north China. A total of 20 virulence genes and 23 AMR genes of 140 isolates collected from 12 farms in six provinces were studied. The antimicrobial susceptibility of 10 veterinary commonly used antimicrobials were tested using the broth microdilution method. Results showed that all the isolates harbored the virulence genes lacIV, gapC, and dltA. The isolates that harbored the genes lacIII, fbsA, hylB, and cfb exhibited the high prevalence (99.29%), followed by isolates that harbored lacI (98.57%), bibA (97.86%), cylE (97.14%), lacII (92.14%), cspA (52.14%), pavA (25%), bca (2.14%), and scpB (0.71%). The fbsB, lmb, spbI, bac, and rib genes were not detected. The virulence patterns of B (fbsA_cfb_cylE_ hylB_bibA_cspA_ gapC_dltA_lacIII/IV) and C (fbsA_cfb_ bibA _ gapC_ dltA_lacIV) were dominant, accounting for 97.86% of the isolates. The following AMR genes were prevalent: pbp1A (97.14%), tet(M) (95.00%), lnu (A) (80.71%), erm (B) (75.00%), tet(O) (72.14%), blaZ (49.29%), tet(S) (29.29%), blaTEM (25.71%), erm (A) (17.14%), erm (C) (13.57%), tet (L) (10.71%), linB (2.86%), and erm (TR) (2.86%). The pbp2b, mecA1, mecC, lnu (D), erm (F/G/Q), and mef (A) genes were not detected. Eighty percent of the isolates harbored AMR genes and were highly resistant to tetracycline, followed by macrolides (10.71%), lincosamides (9.29%) and β-lactams (4.29%). In conclusion, isolates only exhibited well correlation between tetracyclines resistance phenotype and genotype, and almost all isolates harbored intact combination of virulence genes.